Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Pada Distro Kaos Kesu’ di Toraja Utara - Januarto Allolinggi; Dina Ramba; Rati Pundissing (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
This study aims to determine the effect of the marketing mix on consumer decisions at kesu t-shirt distribution in North Toraja. The research data was obtained by using a questionnaire, documentation and direct observation on the kesu t-shirt distribution. The research method used in this research is quantitative research with a total sample of 57 people. The data analysis technique used in this study was multiple linear regression with statistical calculation tools using SPSS version 26. The results of this study obtained the equation Y = 4.172 + 0.105X1 + 0.222X2 + 0.215X3 + 0.095X4. Products influence consumer decisions. Prices affect consumer decisions. Promotion influences consumer decisions. Place influences consumer decisions. Products, prices, promotions, places influence consumer decisions at kesu t-shirt distributions. The determination result (R2) of 0.822 or 82.2% means that the dependent variable namely consumer decision (Y) can be explained by the independent variables product (X1), price (X2), promotion (X3), place (X4). While the remaining 17.8% is explained by other variables outside the variables used.